A Genealogy of the Prose Poem. Issue 2 (August 2017) - Mengham, Rod
Abstract : This article looks at aspects of the genealogy of the prose poem. It does so by tracing correspondences, across a range of texts, in the ways by which characters and writers record themselves 'profoundly sensible' of an 'awful parenthesis that had suspended them', as De Quincey put it, in a place and in a moment of time. The experience of insulation, sequestration, and deep recesses, and then the looping together of ideas of suspension, trance, and syncope are witnessed at work in texts by Dickens, De Quincey, Baudelaire, Henry Mayhew, and Tim Dee, with patterns of influence or similarity discerned therein that are all suggestive of the prose poem's dynamics of containment and extension. Reference is made to representations of this involving both city and field, and to the poetic styles, including parallelism, that work to evoke encroaching and receding horizons.